Tantangan Pendidikan Kewarganegaraan dalam Masyarakat Modern - Nia Ramadhani; Syamzaimar (Suria Academic Press, 2026)
This study aims to analyze the challenges of civic education in modern society and to formulate strategies for strengthening it among digital generations. The research employed a qualitative approach using a library research method through literature searches in Google Scholar, GARUDA, ERIC, Scopus, and accredited national journal portals. The data sources consisted of scholarly journal articles, academic books, proceedings, and relevant educational policy documents, with a focus on publications from the last five years (2022–2026). The literature was selected based on thematic relevance, source credibility, the presence of a DOI or clear publication identity, and full-text availability. The data were analyzed using content analysis through several stages: reading the literature, coding, grouping themes, interpreting relationships among categories, and developing thematic synthesis. The findings reveal that the challenges of civic education are not limited to low digital literacy, the spread of hoaxes, and declining nationalism, but also include the weak internalization of national values, changes in social interaction patterns, and a gap between civic knowledge and students’ civic behavior. These findings indicate that civic education in the modern era remains largely theoretical and has not fully responded to digital social realities. Therefore, strengthening civic education needs to be directed toward the integration of digital literacy, character education, participatory learning, civic engagement, and the contextual use of educational technology. The main contribution of this study is the emphasis that civic education should be understood as a process of building civic awareness that is adaptive, ethical, and participatory in digital spaces. This study offers a framework for strengthening civic education that not only stresses knowledge acquisition, but also develops critical thinking, social responsibility, cultural resilience, and the ability to participate in democratic life.